Macroeconomic Determinants of Coal Exports in Indonesia Amid Global Economic Volatility - Najwa Maulida; P Eko Prasetyo (Journal of Social Research, 2026)
This study analyzes the influence of international coal prices, the IDR/USD exchange rate, interest rates, and China's economic growth on the value of Indonesia's coal exports using the autoregressive distributed lag (ARDL) approach. Data from the 2010–2024 period was used to capture short-term and long-term dynamics relevant to the character of the energy commodity market. The estimation results show that international coal prices have a significant positive effect both in the short and long term, underscoring the role of global prices in determining the export performance of primary commodities. However, the exchange rate has a negative effect in the long term, indicating high import content during the production process; thus, rupiah depreciation increases operational costs in the mining sector. Since Indonesia's exports are highly dependent on China's energy demand as a major trading partner, China's economic growth has a significant positive effect on both time horizons. Meanwhile, interest rates did not significantly affect exports. The significant and large error correction value ensures an adjustment mechanism toward long-term equilibrium. This research provides new knowledge related to export policy and risk management for Indonesia's coal sector amid global economic volatility.